In-vitro Evaluation of Antibacterial Potential of Biocontrol Agents Against Pathogens of Punica granatum L. (International Journal of Food and Nutritional Sciences, 2022)
Pomegranate (Punica granatum L.) is one of the highly valued table fruits, grown in various parts of the world as it has great commercial, medicinal and nutritive value. India is one of the major producers of pomegranates that are exported to various parts of the world and Maharashtra leads in pomegranate production in the country. Thus, in India it is a serious economic threat to pomegranate growers due to lack of effective control measures. Biological control is the most viable approach for the treatment of plant diseases. Thus, there is a need for a safe biocontrol agent. In view of this background, several samples of leaves, fruits, buds and fruits were collected from Pomegranate orchards of Maharashtra for the evaluation of bacterial population and isolation of Trichoderma species. Thus, to evaluate the possibility of their extendable use as biocontrol agents in pomegranate. Pomegranate crop is attacked by several bacterial and fungal pathogens. Thus, these diseases of pomegranate decrease the market value of fruits. Use of bactericides and fungicides is a conventional method to control infections which has hazardous impact on public health and these agrochemicals are not cost effective. Biological control is the most viable approach for the treatment of plant diseases. Thus, there is a need for a safe biocontrol agent and the Trichoderma fungi belong to this category. The biocontrol potential of different Trichoderma species Viz. Trichoderma viride VMB21, Trichoderma reesei VMB23 and Trichoderma stercorarium VMB25. has been demonstrated on Pomegranate bacterial pathogens Viz. Xanthomonas axonopodis VMB13, Xanthomonas campestris VMB15 and Xanthomonas vesicatoria VMB17.